Reporting behaviour change interventions: do the behaviour change technique taxonomy v1, and training in its use, improve the quality of intervention descriptions?. (December 2015) - Wood, Caroline; Hardeman, Wendy; Johnston, Marie; Francis, Jill; Abraham, Charles; Michie, Susan
Abstract Background Behaviour change interventions are likely to be reproducible only if reported clearly. We assessed whether the behaviour change technique taxonomy version 1 (BCTTv1), with and without training in identifying BCTs, improves the clarity and replicability of written reports of observed behaviour change interventions. Methods Three studies assessed effects of using and training in the use of BCTTv1 on the clarity and replicability of intervention descriptions written after observing videos of smoking cessation interventions. Study 1 examined the effects of using and not using BCTTv1. Study 2 examined the effects of using BCTTv1 and training in use of BCTTv1 compared no use and no training. Study 3 employed a within-group design to assess change in descriptions written before and after training. One-hundred and 66 'writers' watched videos of behaviour change interventions and wrote descriptions of the active components delivered. In all studies, the participants' written descriptions were evaluated by (i) 12 'raters' (untrained in BCTTv1) for clarity and replicability and (ii) 12 'coders' (trained in BCTTv1) for reliability of BCT coding. Writers rated the usability and accessibility of using BCTTv1 to write descriptions. Results Ratings of clarity and replicability did not differ between groups in study 1 (allp s > 0.05), were poorer for trained users in study 2 (allp s < 0.01) and improved following training in study 3 (allp s < 0.05). BCT identification was more reliable from descriptions written by trained BCTTv1 users (p < 0.05; study 2) but not simple use of BCTTv1 (p = 0.93; study 1) or by writers who had written a description without BCTTv1, before training (p = 0.50; study 3). Writers reported that using BCTTv1 was difficult but 'useful', 'good' and 'desirable' and that their descriptions would be clear and replicable (all means above mid-point of the scale). Conclusions Effects of training to use BCTTv1 on the quality of written reports of observed interventions were mixed, with some suggestion of improved clarity and replicability of reporting in the within- (study 3) but not the between-group studies (studies 1 and 2). Potential benefits of using BCTTv1 may have been limited by the artificial nature and time constraints of the task.